Grants, loans, and local currencies; their role in foreign aid - Asher, Robert E. (Washington : Brookings Institution, 1961)
The purpose of this study is to help reduce reliance on guesswork by providing a systematic examination of one aspect of the problem: the effects on the level of employment in the United States to be expected in the short run following unilateral reduction in the tariff or other import barriers.
Includes index
Includes bibliographical references.
usc 18/5/18
Loans
Keywords: Economic assistance, American; Foreign exchange